Robust spin-ice freezing in magnetically frustrated Ho2Gex Ti2-x O7pyrochlore - Shukla M.; Upadhyay R.; Tolkiehn M.; Upadhyay C. (My University, 2025)
Structural analysis of spin frustrated Ho2Ge x Ti2-x O7 (x = 0, 0.1, 0.15 & 0.25) pyrochlore oxides has been performed using high resolution X-ray diffraction pattern and low temperature synchrotron X-ray diffraction pattern. The effect of positive chemical pressure on the spin dynamics of Ho2Ge x Ti2-x O7 has been analysed through the study of static (M-T and M-H; magnetisation against temperature & magnetisation against magnetic field) and dynamical (ac susceptibility) magnetic measurements. In lower temperature regime (∼2 K), such systems are predominantly governed by competing exchange (J nn) and dipolar (D nn) magnetic interactions. Magnetic measurements indicate that the application of increased chemical pressure in Ho2Ti2O7 matrix propels the system towards diminished ferromagnetic interaction. Dipolar coupling constant remains almost unchanged but Curie-Weiss temperature (θ cw) reduces to-0.04 K from 0.33 K (for an applied magnetic field; H = 100 Oe) with increasing x in Ho2Ge x Ti2-x O7. Positive chemical pressure establishes the dominance of Ho-Ho antiferromagnetic interaction J nn over dipolar interaction D nn. Spin relaxation feature corresponding to thermally activated single ion freezing (T s∼15 K) is shifted towards lower temperature. This chemical pressure-driven T s shift is ascribed to the alteration in crystal field effect, which reduces the activation energy for singe ion spin freezing. The reduction in the activation energy indicates crystal field-phonon coupling in Ho2Ge x Ti2-x O7 system. The robustness in spin ice freezing (second spin relaxation feature in ac susceptibility curve) remains unaffected with increasingly chemical pressure. This spin freezing ('2 in-2 out' spin arrangement in tetrahedra) is related to quantum tunnelling phenomenon, at T ice ∼ 2 K. It indicates that majority of spins still follows the 'ice rule' in Ho2Ge x Ti2-x O7 even after the application of chemical pressure. © 2020 IOP Publishing Ltd.